2016
DOI: 10.1016/j.vaccine.2015.09.073
|View full text |Cite
|
Sign up to set email alerts
|

Long-term immunogenicity and safety of an investigational herpes zoster subunit vaccine in older adults

Abstract: gE-specific cellular and humoral immune responses persisted for 6 years after two-dose vaccination with HZ/su in healthy older adults. No safety concerns were identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
79
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 107 publications
(87 citation statements)
references
References 21 publications
6
79
0
2
Order By: Relevance
“…1 and Table 1), subsequent experiments focused on Alhydrogel and GLA-LSQ, two clinically relevant adjuvants that generated significant differences in the Pfs25-specific humoral response. Furthermore, the selection of GLA-LSQ as the main comparator to Alhydrogel is supported by the fact that another liposome-based adjuvant system containing a TLR4 agonist and QS21 has been recently approved for clinical use23 and shown to promote durable adaptive immune responses in human vaccine trials2425.…”
Section: Resultsmentioning
confidence: 99%
“…1 and Table 1), subsequent experiments focused on Alhydrogel and GLA-LSQ, two clinically relevant adjuvants that generated significant differences in the Pfs25-specific humoral response. Furthermore, the selection of GLA-LSQ as the main comparator to Alhydrogel is supported by the fact that another liposome-based adjuvant system containing a TLR4 agonist and QS21 has been recently approved for clinical use23 and shown to promote durable adaptive immune responses in human vaccine trials2425.…”
Section: Resultsmentioning
confidence: 99%
“…2,18,19 An investigational herpes zoster subunit vaccine (HZ/su; GSK Vaccines) containing VZV glycoprotein E and the AS01 B adjuvant system is being evaluated for the prevention of herpes zoster and postherpetic neuralgia in adults 50 years of age or older. [20][21][22][23][24][25] A previous trial (Zoster Efficacy Study in Adults 50 Years of Age or Older showed that HZ/su had a vaccine efficacy against herpes zoster of 97.2%, which was consistent across all age groups. 26 Although 24% of the participants in ZOE-50 were 70 years of age or older, the trial was not intended to definitively assess vaccine efficacy against herpes zoster or postherpetic neuralgia in this age group.…”
mentioning
confidence: 88%
“…30,31 Accordingly, HZ/su induces strong glycoprotein E-specific immune responses, including CD4+ T-cell responses, that are preserved with age. 20,24 Moreover, the robustness of the immune responses to glycoprotein E are attributable to the action of the AS01 B adjuvant system, which has also been shown to enhance CD4+ T-cell and humoral immune responses to subunit antigens from other pathogens. 32,33 Together, these results suggest that such adjuvants have the potential to improve the efficacy of vaccines that are intended for use in older adults and other populations that may otherwise have a lower response to vaccination.…”
mentioning
confidence: 99%
“…Few better remedies were available up to 50 years ago, since when antiviral agents and a moderately effective live-attenuated vaccine for prophylaxis have been developed. But hopefully, perhaps as a result of developments in new vaccines,1 and what appear to be prolonged immune responsiveness and safety of such vaccines,24 herpes zoster—and its often chronic, painful sequel of postherpetic neuralgia—will become diseases of the past.…”
Section: ‘Zoster’ ‘Schingles’ and Their Treatmentmentioning
confidence: 99%